OPTIMISING SCREENING FOR OPPORTUNISTIC INFECTION PRIOR TO ANTI-TNF THERAPY. (8th June 2013) - Judge, C; DeGascun, C; Keegan, D; Byrne, K; Mulcahy, H E; Cullen, G; Doherty, G A
Abstract : Introduction: Anti-TNF agents are highly effective for treatment of IBD but are associated with an increased risk of infection. ECCO consensus guidelines have defined screening measured which should be undertaken prior to commencing anti-TNF therapy. Aims/Background: We evaluated how screening practices have changed in recent years, what gaps exist in our approach to screening and how frequently infection risks are identified. Method: A retrospective study of patients who commenced biologic therapy identified from a prospectively maintained database of >3, 000 patients with IBD attending a single centre over a 3 year period. Results: n=225 patients were identified who commenced treatment with either infliximab (IFX, n=144) or adalimumab (ADA, n=81) for treatment of inflammatory bowel disease in a 3 years period from 2010 to 2012. 65% of patients had Crohn's disease, 30% had ulcerative colitis and 5% had IBD-U, undetermined. The proportion of patient who had evidence of screening for Hepatitis B using surface antigen testing (HBsAg) increased significantly from 23% in 2010 to 82% in 2012. However, even in 2012, only 12.5% had antibodies to Hepatitis B core antigen (HBcAb) measured. No patient had a positive HBsAg but 1/13 patients tested had a positive HBcAb. The frequency of screening for latent TB using the quantiferon release assay (QFT) increased from 5% in 2010 to 74% in 2012. 1/64 (1.6%) of the QFT tests was positive resulting treatment for latent TB. One patient who had not undergone QFT testing developed active TB on IFX treatment. Conclusion: This study highlights significant improvements in screening for Hepatitis B and latent TB in patients commencing anti-TNF therapy. Screening for Hepatitis B should incorporate measurement of both HBsAg and HBcAb. Use of a customised request form for screening requests might be valuable in ensuring both assays are performed. The findings also highlights the utility of QFT as a screening test for latent TB.